Why MASLD Lags Behind MAFLD: A Critical Analysis of Diagnostic Criteria Evolution in Metabolic Dysfunction-Associated Liver Diseases - Alboraie, Mohamed; Butt, Amna Subhan; Piscoya, Alejandro; Viet, Hang Dao; Hotayt, Bilal; Al Awadhi, Sameer; Mendez-Sanchez, Nahum (Int Scientific Information, Inc, 2024)
Emerging in the 1800s under the label fat in the liver and later gaining prominence in the 1980 as non-alcoholic fatty liver disease (NAFLD), the disease predominantly attributed to metabolic dysfunction presents a formidable health issue marked by substantial morbidity and mortality. It was 2020 when a change of one letter NAFLD to metabolic dysfunction-associated fatty liver disease MAFLD linked with the change in the definition and diagnostic criteria began a new controversy around the globe. Metabolic dysfunction-associated fatty liver disease (MAFLD) criteria represent a substantial departure from previous diagnostic measures of NAFLD, and provide the first set of positive criteria for diagnosis of the disease in adults and children that emphasise the key attribute of metabolic dysfunction in the pathogenesis, and acknowledges that the disease is a continuum across the life span. In 2023, an adapted version of the diagnostic criteria of MAFLD was proposed to define a slightly modified term; metabolic dysfunction-associated steatotic liver disease (MASLD). The MASLD criteria did not provide any conceptual advantage, and emerging evidence suggests that it actually performs worse than the MAFLD criteria. This raises the intriguing question of why MASLD was unable to take advantage of being second? In this review, we will explore the possible reasons for this unique case and highlight the current evidence supporting the use of MAFLD instead of MASLD in defining metabolic dysfunction-associated fatty liver diseases.
Keywords: Diagnostic Errors; Fatty Liver; Metabolic Diseases; Terminology